La situación de la teoría y terminología de la psicología popular y el futuro de la psicología científica - Braun Gutiérrez, Ricardo (2006)
This article discusses the origins and function of folk psychology and its assimilation in a future scientific psychology. The problems of reductionism in science and eliminativism in psychology are analyzed. The author defends a non-reductive materialism view of psychology and argues for a vindication of the status and role of folk psychology. In this article the unity of science thesis and reductionism are explored and questioned to conclude that taking as an example, the problem of micro-reductions in physics. It is proposed, in contrast, a pluralist standpoint whereby the autonomy and interrelation of the different levels of reality are maintained. The article defends the role of folk psychology, as a source of non-reductive explanations, in the growth of scientific psychology which can be understood in a proposal of two possible uses.